Taxonomic notes on the genus Astragalus (Fabaceae) in Iran, with the description of a new species - Ranjbar, M. (Phytotaxa, 2013)
Astragalus jaldiyanensis is described and illustrated as a new species from Iran. The new species belongs to Astragalus section Hymenostegis. It is closely related to A. assadabadensis, which is a rare species in the subalpine areas of Western Iran. Geographically A. jaldiyanensis is well separated from A. assadabadensis as it occurs in the northwest of Iran. The habit, shape of the calyx and petals are very similar in both species, but the new species differs sufficiently from its relative by having white flowers (vs. yellowish white), leaflets in 8-9 (vs. 4-5) pairs, leaflet size 6-8 x 1.5-2 mm (vs. 15-25 x 2-2.5 mm), keel length 12-13 mm (vs. ca. 16 mm) and peduncle length 7-9 cm (vs. ca. 5 cm). The relationships between the species are discussed. In addition, A. ranjbarii of Astragalus section Dissitiflori is reduced to synonymy of A. ghahremaninejadii.